Claudio Gutiérrez, from logic to epistemology - Camacho, Luis (2024)
We emphasize Claudio Gutiérrez’s influence in the Costa Rican philosophical activity in recent times. After a chronology and a distinction of several stages in his intellectual output, we place his logical work within the history of this science in the country, and then we proceed to the exposition of some of his fundamental ideas in epistemology.